Implementation of Islamic Business Ethics Principles in the Governance of Taska Qalby An Nur Malaysia - Aqilah Hafizhah; Isra Hayati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the implementation of Sharia-based Islamic business ethics principles in the governance of Taska Qalby An Nur, Malaysia, particularly in terms of honesty, trustworthiness (amanah), justice, and transparency in service practices and institutional management. The research employs a qualitative approach using a case study design conducted at Taska Qalby An Nur in Cheras, Selangor, Malaysia. Data were collected through observation, semi-structured interviews with management and educators, and institutional document analysis. Data analysis was carried out descriptively through data reduction, data display, and conclusion drawing. The findings indicate that the application of Islamic business ethics is reflected in daily service practices, communication patterns with parents, and the management’s commitment to service responsibility. This study concludes that strengthening governance based on Islamic business ethics requires continuous value internalization through procedural standardization, enhanced institutional communication, and the development of ethical work practices to build public trust and maintain the quality of early childhood education services.